2019
DOI: 10.28998/2175-6600.2019v11n23p169-185
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da Alfabetização Científica de alunos do 9° ano do Ensino Fundamental de um colégio particular da cidade de São Paulo

Abstract: Atualmente o ensino de Ciências objetiva o desenvolvimento da Alfabetização Científica. Essa é entendida como a aquisição de um conjunto de saberes científicos e tecnológicos que capacita o aluno a operar e se posicionar no mundo em que vive, atuando como um cidadão. Este artigo analisou o nível de Alfabetização Científica dos alunos do 9° ano de um Colégio por meio do Teste de Alfabetização Científica Básica e, também, comparou os Planos de Ensino de Ciências do Colégio com a matriz curricular do programa Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
4
0
5
Order By: Relevance
“…When compared with other studies whose objective was to assess the scientific literacy of students in the third cycle of basic education, or of similar school years (Coppi and Sousa 2019;Jufri et al 2019;Koedsri and Ngudgratoke 2018;Rachmatullah et al 2016;, it is evident that the ALCE results are more positive than the others, since they all revealed that the majority of the students assessed did not obtain the minimum correctness on the items of the instruments to be considered as being scientifically literate. It should be noted, however, that the contexts of application, the assessment instruments used and the number of participants of these studies were not the same as those of the present study.…”
Section: Students' Scientific Literacy Levelsmentioning
confidence: 79%
See 1 more Smart Citation
“…When compared with other studies whose objective was to assess the scientific literacy of students in the third cycle of basic education, or of similar school years (Coppi and Sousa 2019;Jufri et al 2019;Koedsri and Ngudgratoke 2018;Rachmatullah et al 2016;, it is evident that the ALCE results are more positive than the others, since they all revealed that the majority of the students assessed did not obtain the minimum correctness on the items of the instruments to be considered as being scientifically literate. It should be noted, however, that the contexts of application, the assessment instruments used and the number of participants of these studies were not the same as those of the present study.…”
Section: Students' Scientific Literacy Levelsmentioning
confidence: 79%
“…It should be noted, however, that the contexts of application, the assessment instruments used and the number of participants of these studies were not the same as those of the present study. Coppi and Sousa (2019), for example, applied the Test of Basic Scientific Literacy in 189 ninth-grade students from a private school in Brazil. applied a simplified version of the Test of Basic Scientific Literacy in 125 ninth-grade students from a public school, convened with the Federal University of Rio Grande.…”
Section: Students' Scientific Literacy Levelsmentioning
confidence: 99%
“…When compared to the studies that performed this type of analysis, even though used the Test of Basic Scientific Literacy, a difference in the students' scores in the subtests is perceived. In all these studies (CAMARGO et al, 2011;SOUSA, 2019bSOUSA, , 2019aGARCIA, 2015;NASCIMENTO-SCHULZE;WACHELKE, 2006;ÖZDEM et al, 2010;RIVAS;MOÇO;JUNQUEIRA, 2017;VIZZOTTO;DEL PINO, 2020a, 2020bVIZZOTTO;MACKEDANZ, 2018), it was found that the subtest in which students obtained the best performance was in that of the CS and the worst was among the subtests of the NS and ISTS.…”
Section: Resultsmentioning
confidence: 99%
“…This fact may be associated with the difference in emphasis that is given among the competencies of the three subtests by the science subjects of the schools that applied the instrument. Camargo et al (2011) and Coppi and Sousa (2019a) argue that, in Brazil, much importance is given to the contents and competencies belonging to the CS subtest, leaving aside those referring to the NS and ISTS subtests. However, in the Portuguese schools that participated in this study, there seems to be greater dedication to the competences of the latter two subtests.…”
Section: Resultsmentioning
confidence: 99%
“…Dentre os 18 estudos que adotaram o TBSL e as suas versões -TACB, TACB-S, TACB-R e adaptadas -, Camargo et al ( 2011), Gresczysczyn et al (2018), Laugksch e Spargo (1996a), Lima e Garcia (2015), Oliveira e Silva-Forsberg (2012), Rivas et al (2017), Vizzotto e Del Pino (2020a, 2020b e Vizzotto e Mackedanz (2018) revelaram que a maioria dos alunos avaliados é cientificamente literata. Já os estudos de Coppi e Sousa (2019a, 2019b, Laugksch e Spargo (1999), Lima e Garcia ( 2013 Nas sete pesquisas restantes, as quais aplicaram diferentes instrumentos de avaliação da literacia científica, os estudos de Atta e Aras (2020), Brossard e Shanahan (2006) e Rundgren et al (2010) revelaram médias de acertos nos itens acima dos 50%, ao passo que os estudos de Jannah et al (2020e Jufri et al (2019 indicaram médias abaixo dos 50% e o de Koedsri e Ngudgratoke (2018) relatou que os alunos não dominam os três atributos de literacia científica avaliados. Soobard e Rannikmäe (2011) reportaram que 54% dos alunos possuem um nível funcional de literacia científica.…”
Section: Resultados Dos Estudos: Desempenho Na Avaliação Da Literacia...unclassified